Wave packet and quasiclassical trajectory calculations for the N(2D)+H2 reaction and its isotopic variants - Castillo, J. F.; Bulut, N.; Banares, L.; Gogtas, F. (Elsevier, 2007)
The N(D-2) + H-2(v = 0, j = 0) reaction and its HD and D-2 isotopic variants have been studied by means of quantum mechanical real wave packet and wave packet with split operator and quasiclassical trajectory methodologies on the potential energy surface of Ho et al. [J. Chem. Phys. 119 (2003) 6]. Total initial state-selected and final state-resolved reaction probabilities and product rotational distributions have been calculated for total angular momentum J = 0 in a broad range of collision energies. The real wave packet results are in very good agreement with the corresponding split operator wave packet calculations. A reasonable overall good agreement has been found between the wave packet and quasiclassical trajectory results. Integral cross-sections and thermal rate constants have been calculated from the wave packet reaction probabilities by means of standard J-shifting, refined J-shifting and uniform J-shifting methods in combination with the centrifugal sudden approximation for J > 0. Comparisons with available exact wave packet, quasiclassical trajectory and experimental results are made and discussed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: reaction dynamics; quasiclassical trajectory method; wave packets; insertion reactions